If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + -7 = 5x + 4 Reorder the terms: -7 + 3x = 5x + 4 Reorder the terms: -7 + 3x = 4 + 5x Solving -7 + 3x = 4 + 5x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-5x' to each side of the equation. -7 + 3x + -5x = 4 + 5x + -5x Combine like terms: 3x + -5x = -2x -7 + -2x = 4 + 5x + -5x Combine like terms: 5x + -5x = 0 -7 + -2x = 4 + 0 -7 + -2x = 4 Add '7' to each side of the equation. -7 + 7 + -2x = 4 + 7 Combine like terms: -7 + 7 = 0 0 + -2x = 4 + 7 -2x = 4 + 7 Combine like terms: 4 + 7 = 11 -2x = 11 Divide each side by '-2'. x = -5.5 Simplifying x = -5.5
| 2+-1.5+0.5= | | 4(7x+8)=6(8x-11)-2 | | -69=-7-p | | Y=-5x+12 | | 42+3x=180 | | -3n-1=-37 | | -3n-=-37 | | 12-(-x)+8=18 | | 2a-5=-38 | | -4=-3t+2 | | 4y=5x+12 | | Y=5x+12 | | 15k-4=21 | | (4w+1)(6+w)=0 | | 8a-12=6 | | (3x^2)-8x=0 | | 4x-3(2x-3)=11 | | 0.7(3x-5)+3.9=14.5 | | -9=3+6k | | 3b-2(b+4)=8(b-1) | | x-4+6x-8x=3 | | 3(4X-3)=-81 | | 8(2x+3)-5=16x+19 | | -7(3v+6)=-7v+32 | | 3(x-7)=23-(3x+2) | | 6(4X+4)=24 | | -63+105= | | 18-m=9+3 | | -37=3w+11-7w | | -9*7= | | 4(5-n)=-16 | | 7y-12=4y+6 |